2012
DOI: 10.1254/jphs.12002fp
|View full text |Cite
|
Sign up to set email alerts
|

Renal Protection of In Vivo Administration of Tempol in Streptozotocin-Induced Diabetic Rats

Abstract: The present study was carried out to investigate the protective effects of tempol on renal function and the underlying mechanism in streptozotocin-induced diabetic rats. The diabetic rats were randomly divided into Model group (without tempol) and Tempol group. Nondiabetic rats were served as Control group. The mRNA expression of canonical transient receptor potential 6 (TRPC6), transforming growth factor (TGF)-β1 and type IV collagen (Col IV) were examined. The malondialdehyde (MDA) level, activities of super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 54 publications
4
12
3
Order By: Relevance
“…On the basis of these findings, pitavastatin appeared to have anti-oxidation independent action. On the other hand, Luan et al [35] reported that 6-week treatment with tempol in diabetic rats significantly ameliorated the renal dysfunction and pathological changes in glomeruli, and our findings were inconsistent with their results. We cannot clearly explain the reason of these discrepancies, but our 3-week study period was the half time of theirs, which might cause these discrepant results.…”
Section: Discussioncontrasting
confidence: 99%
“…On the basis of these findings, pitavastatin appeared to have anti-oxidation independent action. On the other hand, Luan et al [35] reported that 6-week treatment with tempol in diabetic rats significantly ameliorated the renal dysfunction and pathological changes in glomeruli, and our findings were inconsistent with their results. We cannot clearly explain the reason of these discrepancies, but our 3-week study period was the half time of theirs, which might cause these discrepant results.…”
Section: Discussioncontrasting
confidence: 99%
“…Increased PCOs in the kidney of SHADR group was associated with a significant reduction in the antioxidant enzyme activities of kSOD and kGSH-Px. These results were consistent with the findings described by others in diabetic rats [11], and ADR-induced nephropathy models [22,2830]. Taking into account that peroxynitrite when acts as an oxidant produces nitrite and hydroxide ion rather than isomerizing to nitrate [33], we hypothesized that the increased nitrite production in the kidney of SHADR and the reduced level of nitrate that we observed compared to SHC, indicated an elevated level of peroxynitrite induced protein oxidation in this group, thus in conditions of reduced kidney antioxidant defense contributed to the deterioration of renal structure and function in this model of proteinuric nephropathy.…”
Section: Discussionsupporting
confidence: 94%
“…The alterations in renal function in SHR with ADR nephropathy, as noticed by the development of massive proteinuria in this study, were also accompanied by a significant reduction of SOD and GSH-Px activities in the kidney. The above findings are consistent with those previously reported in diabetic and ADR-induced nephropathy [11,2830]. Because ADR accumulates mainly in the kidney [31], and given that the kTBARS remained unchanged after ADR treatment in the present study, similar to results obtained by Zima et al in Wistar rats [32] or in BALC/c mice with early ADR nephropathy one week after application of 10mg/kg [28], we performed protein carbonyl test to find out whether protein carbonilation, an irreversible process induced in vivo by all types of reactive oxygen and nitrogen species including peroxynitrite, and followed by loss of enzymatic activities, loss of ligand binding properties, increased susceptibility to proteolytic activities, aggregation, and modification in the transcriptional activities [7], could participate in ADR-induced nephropathy in SHR.…”
Section: Discussionsupporting
confidence: 94%
“…However, tempol has previously been shown to reduce urine flow in diabetic animals. 38 The reduced cortical RBF in diabetic kidneys, despite unaltered total RBF, may relate to a technical issue when using the laser Doppler technique on kidneys with different stages of hypertrophy. It is also unlikely that augmented oxygen delivery, secondary to increased hematocrit caused by the HIF activation, is a major contributor to the mitigated intrarenal hypoxia, because intrarenal pO 2 in the diabetic kidney mainly is determined by QO 2 .…”
Section: Discussionmentioning
confidence: 99%